Assessing multimodal literacies in science: semiotic and practical insights from pre-service teacher education. (3rd March 2020) - Jones, Pauline; Turney, Annette; Georgiou, Helen; Nielsen, Wendy
ABSTRACT: This paper arises from research undertaken by educational semioticians and science educators investigating the use of student generated digital artefacts as assessment tasks in pre-service science teacher education. Part of a broader shift toward student-generated media in tertiary science, the use of such tasks is driven by the need to deepen pre-service primary teachers' understandings of content and to foster enthusiasm for teaching science. However, the tasks are challenging as students must demonstrate both content and meta-semiotic knowledge in these brief digital standalone presentations. In the paper, we draw on artefacts, interviews and assessment practices to demonstrate these challenges. We identify what have emerged as key semiotic understandings necessary to complete a successful response to the task, arguing that these include multimodal understandings as well as knowledge of disciplinary specific representational practices. We describe an intervention informed by functional social semiotics and scaffolded literacy approaches with key features including use of an exemplar text for deconstruction and an explicit instructional sequence with a tailored assessment rubric. The paper reports both theoretical and practical insights and seeks to contribute to emerging analytical frameworks as well as multimodal literacy assessment.